Flower morphology and ontogeny of endemic Crataegus tanacetifolia (Lam.)Pers. (Rosaceae) from Turkey - ÇETİNBAŞ GENÇ, ASLIHAN (My University, 2020)
Abstract: In this study, flower morphology and ontogeny of Turkish endemicCrataegus tanacetifolia(Lam.) Pers. (Rosaceae) were studied using stereo, light and scanning electron microscope. Crataegustanacetifoliahas corymb type of inflorescence which bears 5-10 hermaphrodite flowers. The first sign in appearance of the flowers is the differentiation of apical meristem as a roundish bulge. It transforms into the floral meristem which gives rise to floral organ primordia in advanced stages. Twentystamen primordia differentiate as roundish bulge from the sides of floral meristem. Subsequently, the stamen primordia start stretching and differantiating into filaments and anthers respectively. After a short time of stamen initiation, 5 carpel primordia differentiate from the floral meristem. In following stages, the carpel primordia elongate and form an ovary with 5 loculi. During the ovary formation, 5 styles occur on the ovary and then stigmas evolve out of styles tips.

Bu çalışmada, Türkiye endemiği Crataegus tanacetifolia(Lam.)Pers.’in (Rosaceae) çiçek morfolojisi ve ontogenisi stereo, ışık ve tarayıcı elektron mikroskobu ile incelenmiştir. Crataegustanacetifolia 5-10 adet hermafrodit çiçek taşıyan korimbus tipi çiçek durumuna sahiptir. Çiçeklerin ortaya çıkışındaki ilk işaret, apikal meristemin yuvarlak bir çıkıntı olarak farklılaşmasıdır. Apikal meristem ilerleyen evrelerde çiçek organlarını oluşturacak olanfloral meristeme dönüşür. Floral meristemin kenarlarından 20 adet stamen taslağı yuvarlak çıkıntılar olarak farklılaşır. Ardından stamen taslakları uzamaya başlar ve sırası ile filamentler ve anterleri oluşturur. Stamen taslaklarının belirmesinden kısa bir süre sonra, floral meristemden 5 adet karpel taslağı farklılaşır. İlerleyen evrelerde, karpel taslakları uzar ve 5 lokuslu bir ovaryum oluşturur. Ovaryum oluşumu esnasında, 5 stilus ovaryumun üzerinde gelişir ve ardından stilusların üzerinde stigmalar geişir.
Türkiye endemiği Crataegus tanacetifolia (Lam.)Pers.’ in(Rosaceae) çiçek morfolojisi ve ontogenisi